Leadership Styles and Employees’ Job Performance at Forestry Research Institute of Nigeria - Kamilu Kolade Bolarinwa; Simeon Ajayi; Oyinade Adenuga,; Elijah Obayelu (Journal of Agricultural Extension, 2023)
The study examined leadership styles and employees’ job performance in the Forestry Research Institute of Nigeria (FRIN). A total of 120 employees were chosen at random from among the 900 FRIN employees. Percentages, means, standard deviation and regression were used for the analysis. Results showed that the majority (89.2%) of the employees displayed transformational leadership styles while 87.5% of the employees were democratic in their leadership styles. Indicators of autocratic leadership style include: superiors telling subordinates what to do, how to do it, and when they want it done ( =3.6). Indicators of laissez-faire leadership style include employees responsible for defining his or her own job ( = 3.01). Aspects of job performance influenced by the leadership styles of employees include: efficiently managing information and data (  = 4.10) and achieving deadlines ( = 4.10).  Transformational (78.5%) and democratic styles (54.3%) caused (variations in employee job performance. The organization made used of transformational and democratic leadership styles more than other leadership styles. The organisation should encourage the use of the two styles and mix it with other leadership styles where necessary in order to improve the administrative strength and achievement of organisational goals